2019
DOI: 10.1080/21548331.2019.1650608
|View full text |Cite
|
Sign up to set email alerts
|

Healthcare-associated infections including neonatal bloodstream infections in a leading tertiary hospital in Botswana

Abstract: Background: Healthcare-associated infections (HAIs) increase morbidity, mortality, length of hospital stay and costs, and should be prevented where possible. In addition, up to 71% of neonates are prone to bloodstream infections (BSI) during intensive care due to a variety of factors. Consequently, the objectives of this study were to estimate the burden of HAIs and possible risk factors in a tertiary hospital in Botswana as well as describe current trends in bacterial isolates from neonatal blood specimen and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
18
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 58 publications
2
18
1
Order By: Relevance
“…The HAI prevalence from our research in Fiji is similar or slightly lower than estimates from other studies in LMICs which also used ECDC criteria, such as 8.2% in Ghana, 8.4% in Pakistan, 13.5% in Botswana and 11.5% across four Latin American countries [ 21 23 ]. Compared to high-income settings, Fiji’s HAI prevalence is higher than that reported in the USA (3.2%), Europe (6.5%), and Japan (7.4%) but lower than rates in Australia (9.9%) and Singapore (11.9%) [ 17 20 , 28 ].…”
Section: Discussionsupporting
confidence: 66%
See 1 more Smart Citation
“…The HAI prevalence from our research in Fiji is similar or slightly lower than estimates from other studies in LMICs which also used ECDC criteria, such as 8.2% in Ghana, 8.4% in Pakistan, 13.5% in Botswana and 11.5% across four Latin American countries [ 21 23 ]. Compared to high-income settings, Fiji’s HAI prevalence is higher than that reported in the USA (3.2%), Europe (6.5%), and Japan (7.4%) but lower than rates in Australia (9.9%) and Singapore (11.9%) [ 17 20 , 28 ].…”
Section: Discussionsupporting
confidence: 66%
“…With neonatal ICU patients excluded, the HAI prevalence among children in our study was only 4.4% (3/69). Other recent PPSs from LMICs also include similarly high proportions of paediatric (from 15 to 26%) [ 21 24 ] and obstetric (from 19 to 30%) [ 21 , 23 ] patients, whereas recent studies from high-income countries showing higher HAI prevalence excluded paediatric patients [ 18 , 19 ]. Third, inpatients in Fiji may not have been as sick as those in other studies, although no comorbidity data was collected to allow direct comparison.…”
Section: Discussionmentioning
confidence: 99%
“…From the study, the national pooled prevalence of HCAI in Ethiopia was 16.96% (95% CI: 14.10%-19.82%). The result was higher than studies conducted in China (3.12%) [ 35 ], Morocco (10.3%) [ 36 ], Botswana (13.54%) [ 6 ], and South Africa (7.67%) [ 7 ]. The possible reasons for high prevalence in this study might be very low hand hygiene practice by physicians and resource constraints [ 37 ], low adherence to infection prevention practice [ 38 ], low level of job satisfaction [ 39 ], morally distressed nurses [ 40 ], and low implementation of the nursing process [ 41 ] in our settings, and also less attention given to HCAI.…”
Section: Discussionmentioning
confidence: 59%
“…Though data is scarce, the burden of HCAI was found to be high in Sub-Saharan Africa (SSA) countries [ 5 ]. Specifically, the prevalence of HCAI was noted in Botswana (13.4%) [ 6 ], South Africa (8%) [ 7 ], and Ethiopia (13% to 22%) [ 8 – 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Nosocomial infection (NI) was found between 1.6 and 28.7% in Sub-Saharan Africa [ 4 ]. Specifically, the overall prevalence of HCAI was found in Botswana (13.4%) [ 5 ] and South Africa (8%) [ 6 ]. Regarding types of HCAI, a meta-analysis showed that RTI, UTI, SSI, and BSI from highest to lowest magnitude in order were found worldwide, but SSI (51.1%) was the leading in Africa [ 7 ].…”
Section: Introductionmentioning
confidence: 99%